Peran Kelompok Kerja Pendampingan dan Perlindungan Anak GKJW Mewujudkan Gereja Ramah Anak - Oktavia Yermiasih; Imanuel Teguh Harisantoso; Gunawan Yuli Agung Suprabowo (Integritas: Jurnal Teologi, 2023)
This article disscusses about the role of Child Assistance and Protection Working Group (Pokja P2A) to create a Child-Friendly Church. Children are vulnerable categories who need assistance and protection. The assistance and protection can be inform of fulfilling children’s rights which become the responsibility of all parties, including the church. We can call Child-Friendly Churches for these kind of churches who take responsibilities in fulfilling children’s rights, so that holistic assistance is realized. GKJW as one of the churches that serves children formed the Child Assistance and Protection Working Group (Pokja P2A) to realize this holistic mentoring. Therefore, this study aims to find out the meeting point between the Child-Friendly Church and the Pokja P2A GKJW then analyze how the pastoral role of the Pokja P2A GKJW in realizing a Child-Friendly Church. This research was conducted using a qualitative approach with data collection methods in the form of interviews, observations, and literature studies involving GKJW Bondowoso as research subjects. Through this research, it was found that the assistance provided by the Pokja P2A contained holistic pastoral care elements. Therefore, Pokja P2A has many roles, namely as a companion, facilitator, promoter, and educator in terms of realizing a Child-Friendly Church.